Using Multisensory on The Ability To Recognize Letter Sounds and Forms of Children - Rakhmawati, Nur Ika Sari; Hasibuan, Rachma; Reza, Muhammad (Universitas Negeri Semarang, 2018)
This study is aimed to know (1) The effect of multisensory on the ability to recognize the letter sounds of children aged 4-5 years?, (2) The effect of multisensory on the ability to recognize letter forms of children aged 4-5 years?, (3) The relationship of ability to recognize letter sounds and forms of children aged 4-5 years?, (4) simultaneous interaction between the use of multisensory on the ability to recognize letter sounds and forms of children aged 4-5 years? This study uses Quasi Experimental Design, with Nonequivalent Control Group Design. This design is similar to the pretest - posttest control group design where, the experimental group or the control group is not randomly selected. The error sampling was 5% with 78 children. The results can be concluded as follows; the students' ability to recognize letter sounds in the control group and experimental group is significantly different, where the obtained T test after treatment is -3.204 with sig value (probability) of 0.003 referring to average score of control group of 35.18 and group experiment of 41.58. The children's ability to recognize letter forms in the control group and experimental group show that the obtained T test after treatment was of -0.042 with sig value (probability) of 0,000 referring to the average score of the control group of 45.891 and experimental group of 50.63 . The correlation between the ability to recognize letter sounds and forms in the control group is 0.905 and 0.826 in the experimental group, meaning that it has the strong correlation, where if children's ability to recognize letter sounds is good so ability to recognize letter forms is good as well. Therefore, it can be concluded that the direct use of multisensory makes children easier to learn.